Conservation Planning and Reporting Implications of qPCR-based Multi-species eDNA Detection Under EU Environmental Regulations - Simone Giovacchini; Enrico Mirone; Antonia Bruno; Fausto Ramazzotti; Luca Caprotti; Pamela Monaco; Mirko Di Febbraro; Chiara Manfrin; Pushpinder Singh Jamwal; Francesco Belluardo; Andrea Galimberti; Anna Loy (Environmental Management, 2026)
European Union (EU) legislation supports the conservation of endangered freshwater species through the Habitats Directive (HD, 92/43/EEC) and the Water Framework Directive (WFD, 2000/60/EC), and the eradication of Invasive Alien Species (IAS) through the Regulation 1143/2014. Periodic monitoring and reporting on the species listed in these regulations are mandatory for EU Member States. Quantitative PCR environmental DNA (qPCR eDNA) based approaches offer a new cost-effective and sensitive tool that could contribute to these monitoring obligations and to spatial conservation planning. We analysed the results from a qPCR eDNA simultaneous survey of 11 endangered species, four IAS, one pathogen fungus and one translocated fish at 53 central-Italian freshwater sites to produce three scores that could be used to prioritize areas of intervention based on the cumulative presence of native and alien species and their prevalence and co-occurrence. For each site, we proposed a Prioritizing Protection Score (PPS), a Prioritizing Eradication Score (PES), and a Benthic Invertebrates and Fish Score (BIFS) in accordance with HD, Regulation 1143/2014, and WFD. PPS prioritized 39 sites eligible for Natura 2000 designation to achieve the EU target of 30% protected land, PES identified 22 sites for IAS eradication and management, whereas BIFS highlighted 33 sites where freshwater evaluations can benefit from eDNA surveys. Results from the qPCR eDNA survey also revealed 53 new grid cells of occurrence of IAS and species listed in Annexes II, IV and V of HD that will contribute to the next reporting for both the HD and the IAS Regulation.